Fascist youth organizations and propaganda in a transnational perspective : Balilla and Gioventù italiana del Littorio all’estero in Argentina (1922-1955) - Katharina Schembs (Amnis)
In aiming at rejuvenation of politics Italian Fascism conceded the indoctrination of youth as guarantors of the regime’s durability a central role. This was not only to be achieved in school but also during leisure time in the form of the Fascist youth organizations. Drawing from different external sources of inspirations, the resulting Opera Nazionale Balilla (ONB) and Gioventù Italiana del Littorio (GIL) themselves came to be models for organizing youth in other countries. In the course of the Fascist ideological expansionism, the youth organizations were considered an important instrument of propaganda abroad. Apart from Europe special attention was paid to overseas countries with large Italian immigrant communities like the USA, Brazil and Argentina. In putting the Fascist youth organizations into a transnational perspective, the main focus of the article is on their propagandistic activities in Argentina as a country with a large population of Italian descent. Likewise the reception and reaction of the Italian immigrant community and the host society are taken into account. Lastly, an outlook is given on the afterlife of the Fascist youth organization as an inspirational source during Peronism (1946-1955).